(untitled) (Società e diritti, 2024)
The latest achievement of Baldassare Pastore’s legal-philosophical reflection is a dense analysis of the contemporary landscape which reflects its heterogeneous, protean texture, crossed by still strong jolts of change and innovation. Although the science of law has been marked by a sort of vertigo of change for more than three decades now; from a twilight tone, compared to consolidated patterns and openness to conceptual innovations. Pastore’s reflection outlines a clear picture of the present processes, proposing a conception of law and the activity of jurists as collective practice and practical (juridical) reason, because it is aimed at social action, very convincing for its ability to contain the multiple elements (even in dialectic with each other) of the phenomenology of law. At the same time, it constitutes an opportunity to highlight some profiles with respect to which legal theory seems to have been distracted, if not downright reticent